2021
DOI: 10.1186/s12879-021-06581-y
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of factors associated with SARS-CoV-2 infection among healthcare workers in Colombia

Abstract: Background Healthcare Workers (HCW) are repeatedly exposed to SARS-CoV-2 infection. The aim of this study was to identify factors associated with SARS-CoV-2 infection among HCW in one of the largest cities in Colombia. Methods We conducted a case–control study, where cases had a positive reverse transcription-polymerase chain reaction and controls had a negative result. Participants were randomly selected and interviewed by phone. Analyses were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
1
16
0
3
Order By: Relevance
“…Among these, 104 were excluded (Supplementary File 2). 16 full text articles were screened for eligibility [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], 6 were excluded [ 24 , 28 , 31 , 32 , 33 , 36 ] and ultimately 10 eligible studies were included in this review and meta-analysis. Reasons for exclusion at full text review stage included lack of PCR confirmation of COVID-19 infection [ 24 , 31 , 32 , 33 , 36 ], and lack of evidence on risk estimates for COVID-19 risk factors [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 104 were excluded (Supplementary File 2). 16 full text articles were screened for eligibility [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], 6 were excluded [ 24 , 28 , 31 , 32 , 33 , 36 ] and ultimately 10 eligible studies were included in this review and meta-analysis. Reasons for exclusion at full text review stage included lack of PCR confirmation of COVID-19 infection [ 24 , 31 , 32 , 33 , 36 ], and lack of evidence on risk estimates for COVID-19 risk factors [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for exclusion at full text review stage included lack of PCR confirmation of COVID-19 infection [ 24 , 31 , 32 , 33 , 36 ], and lack of evidence on risk estimates for COVID-19 risk factors [ 28 ]. Studies included were conducted in China [ 34 , 35 , 37 ], USA [ 26 , 29 ], India [ 23 , 27 ], Italy [ 25 ], Spain [ 30 ] and Colombia [ 38 ]. Of the studies included, 3 were retrospective cohorts [ 34 , 35 , 37 ], 2 were prospective cohorts [ 26 , 29 ], 3 were case controls [ 23 , 27 , 38 ] and one was a cross sectional [ 30 ] and one case series [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Using a cough simulator, face shields blocked 97% of large particle transmission to the providers' respirator mask, blocking disease transmission through facial mucous membranes. [4] A casecontrol study identified PPE misuse as a significant risk factor for HCP COVID-19 infection, [5] and a recent systematic review has shown significant reductions in HCP COVID-19 infection with the fastidious use of face shields. [6] During the initial wave of COVID-19, many aspects of the worldwide supply chain were interrupted by lockdowns, sourcing competition, export bans, and other distribution disruptions.…”
Section: Introductionmentioning
confidence: 99%